Central African Economic and Monetary Community : Staff Report on Common Policies of Member Countries; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Central African Economic and Monetary Community. (IMF Staff Country Reports; Country Report ;, 2011)
Member countries of the Central African Economic and Monetary Community are recovering from the global financial crisis, although growth in 2011 has not returned to precrisis levels. Executive Directors welcomed the region's economic recovery from the global financial crisis and its overall positive outlook. Directors noted, however, that the recovery has been uneven across member countries and that inflation is on the rise owing to high international food and fuel prices. Directors encouraged the authorities to adopt an appropriate policy mix to contain inflationary pressures in the short term.